Upaya Masyarakat Daerah Pariwisata Candidasa Kabupaten Karangasem dalam Mempertahankan Keberadaan Bahasa Bali - I Putu Pande Suargita; I Ketut Sudarsana (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2017)
In the use of Balinese language in the community of Candidasa tourism area, there are some obstacles encountered by the community, namely the lack of interest to learn the language of Bali, the influence of association, and because of the social class in the community. To preserve the existence of Balinese language, the people of Candidasa tourism area made several efforts, namely introducing Balinese language early, using Balinese language in family environment, and instilling a sense of love of Balinese culture.